0342 Use of a Diffused Fragrance Before Bed May Contribute to Improved Objective and Perceived Sleep. (25th May 2022) - Rus, Holly; Danoff-Burg, Sharon; Weaver, Morgan; Rodriguez, Rodolfo; Gavrilova, Larisa; Gottleib, Elie; Lillford, Stephen; Raymann, Roy
Abstract: Introduction: This study examined if a diffused fragrance used at home before bedtime would contribute to sleep improvement in a sample of healthy females. Existing evidence regarding the sleep-promoting properties of fragrances often has been anecdotal or based on clinical research, thereby limiting the generalizability and ecological validity of results. Methods: 26 women with self-reported interest in air care to support healthy sleep participated in a 9-week field study. A within-subjects, counterbalanced intervention design was implemented, comparing 3 weeks of nightly product use to 3 weeks without using the product after a baseline period. Intervention consisted of the use of a fragrance diffuser and fragrance by Reckitt's Scientific Platform Fragrance Research for at least an hour at the participants' preferred settings in the room where they spent the most time before going to bed. Sleep was measured objectively with SleepScore Max every night. Self-report data were collected at bedtime, in the morning, and after each measurement period. Multilevel regression and paired t-tests were used to test for statistical significance. Results: Across all participants there were 835 nights of tracked sleep. Participants (100% female, age 21 to 55, average 36 years old) showed improvement in both objective and perceived sleep during the intervention. Participants got more deep sleep, spent a greater proportion of the night in deep sleep, and had an improved BodyScore, a measure of deep sleep (ps<.05). Additional objective improvements were related to sleep consistency: fewer awakenings during the night, less time awake during the night, and better sleep maintenance (ps<.05). Self-report results complemented the objective findings. Participants felt sleepier at bedtime, felt they woke up less often and spent less time awake after initially falling asleep, reported better sleep quality, and experienced better mood both at bedtime and in the morning (ps<.05). No significant negative impacts were seen on sleep in the objective and self-report measures. Conclusion: Using the fragrance diffuser before bed may contribute to improvement of many aspects of sleep within this study population of females without underlying sleep conditions. Objectively improved sleep outcomes were supported by self-report, showing multifaceted benefits of the diffused fragrance on sleep. Support (If Any): Reckitt